Antifouling effect of water-soluble phosphate glass frit for filtration plants - Shim, Kyudae; Abdellatif, Mohamed; Park, Jeryang; Kim, Dongkyun (Folia microbiologica, 2020)
The antifouling, antimicrobial, elution behavior, skin irritant, and cytotoxicity properties of water-soluble phosphate glass on stainless steel were evaluated. Water-soluble phosphate glass samples with 35% Cu (mol/mol) were prepared by altering the network modifier (Na2O, K2O) and network former (P2O5, B2O3) compositions. The materials were melted at temperatures within the range of 850-950 °C. The melt was then quenched and ground into fine particles using a twin roll mill. The resulting water-soluble glasses were prepared as glass frit (size < 100 μm) using a sieve. The amorphous phase was determined by X-ray diffraction and differential thermal analysis. Water-soluble glasses with a reduced Cu ion elution rate of 1.2 ppm per week were formed because the chemical resistances of the formulated glasses improved as the P2O5 content decreased and the B2O3 content increased. To test its antifouling properties, the glass frit was mixed with paint and coated onto a STS316L sheet. The surface roughness was increased markedly from 1.4 to 19.2 nm, increasing the specific surface area for antimicrobial activity. It was demonstrated that the proposed method was able to form noncytotoxic, nonirritant, water-soluble glasses with 99.9% antimicrobial activity against Staphylococcus aureus. These results suggest that water-soluble phosphate glass on STS316L sheets could be useful in filtration plants.
Keywords: Animals; Glass; Rabbits; Antimicrobial activity; teplota; Antifouling effect; čištění vody; Water-soluble glass frit; Anti-Bacterial Agents; kůže; bioznečištění; filtrace; Staphylococcus aureus; Temperature; Phosphates; Water Purification; X-Ray Diffraction; difrakce rentgenového záření; Skin; sklo; králíci; zvířata; Filtration; Biofouling; antibakteriální látky; fosfáty; Cytotoxicity